Can annual land use plan control and regulate construction land growth in China?. (December 2020) - Zhou, Yan; Huang, Xianjin; Zhong, Taiyang; Chen, Yi; Yang, Hong; Chen, Zhigang; Xu, Guoliang; Niu, Lede; Li, Hehui
Graphical abstract: Highlights: Effectiveness of annual land use plan on controlling construction land growth is examined. Construction land growth is closely related to the implementation intensity of the annual land use plan. The implementation of the annual land use plan is described as effective though not completely successful. Abstract: Annual land use plan (ALUP) stands for the quota allocation of land converted to non-agricultural use, which has been in place since 1987 in China. Although the ALUP has been implemented for more than 30 years and has played an important role in China's non-agricultural land growth management, little has been done to assess the effect of its implementation. The purpose of this research is to evaluate the effect of the ALUP on controlling the growth of construction land in China. The province-level data on land use in China during the period of 2006–2013 were collected and then analyzed using panel data model. The results show that (1) the ALUP can effectively curb construction land growth, and the construction land decreased about 1721 ha with a 1% increment of the intensity of growth management. Construction land growth is closely related to the implementation intensity of the ALUP, which decreases 30, 892 ha under strict implementation but increases an extra 181, 451 ha with relaxed implementation; (2) the implementation effect of the ALUP shows significant differences between provinces, and the provinces of northwestern and eastern China show better performance than provinces from the southwest and central regions. National development strategy and region's differentiation land policy may have contributed to this phenomenon; (3) taking both the goal achievement and effectiveness into account, the implementation of the ALUP is described as effective though not completely successful; and (4) for more efficiency and success, the study proposes some suggestions on improving policy implementation in the future.